Determinants of Sale Response Probability and Tourism Backward Linkage with Local Micro and Small Enterprises of Kisumu County – Kenya - Mathias, Amata Mwalo; Nyongesa, Destaings N (Journal of Tourism Management Research, 2020)
Tourism backward linkage with local enterprises in an economy enhances its economic impact. However, high income leakages experienced in Sub Sahara Africa especially in Kisumu County in Kenya indicate limited tourism linkage. The aim of the study was to find significant factors explaining extent of tourism backward linkage with economy of Kisumu County and factors influencing probability of local sales as proportion of total sales surpassing a national government threshold of 30%. Across section survey of 106 randomly selected tourism enterprises was conducted in Kisumu County. Linear probability and multiple linear regression models were developed to explain variables with significant effect on changes in response probability and local purchase ratio respectively. It was established that local purchase ratio in rural area of Kisumu County was higher than that obtaining in the outskirts of Kisumu Town and CBD of Kisumu Town by 15.3%. Increasing number of employees in local supplier business and rate of weekly local supplies reduced the probability of sale of such supplier exceeding 30% of all purchases made by tourism enterprise by 7.4% and 5.3% respectively. But quality of local supplies enhanced probability of exceeding 30% threshold by 8.8%. In conclusion location of tourism enterprises affected tourism backward linkages with local businesses. Though quality of local supplies enhanced penetration of local business activities in tourism sector, number of employees in suppliers` enterprise and higher weekly rate of supplies depressed it.